Bimolecular Intermolecular-Michael/Intramolecular-Michael/Aromatization Reaction of 1-Cyanocyclopropane 1-Esters or 1,1-Dicyanocyclopropanes: A Straightforward Approach to Fully Substituted Benzenes - Ye, Weijian; Zhou, Lanxiang; Xue, Shuwen; Li, Yang; Wang, Cunde (Synlett, 2015)
An efficient and straightforward synthetic protocol has been developed for the preparation of fully substituted benzenes via a [3+3]-cyclodimerization reaction of 1-cyanocyclopropane 1-esters or 1,1-dicyanocyclopropanes for the generation of a wide range of structurally interesting significant compounds. The reaction utilizes Et3N-promoted C–C bond cleavage, two new C–C bond formations of 1-cyanocyclopropane 1-ester and simultaneous aromatization by removal of cyano and ester groups in a domino fashion.
Keywords: [3+3]-cyclodimerization; donor–acceptor cyclopropane; 1-cyanocyclopropane 1-ester; fully substituted benzene; aromatization